Study on Cardiac Ischemia and Ischemia/Reperfusion Cause Wide Proteolysis of the Coronary Endothelial Luminal Membrane: An Approach to Possible Dysfunctions - Arroyo-Flores, Blanca; Chi-Ahumada, Erika; Briones-Cerecero, Erika; Barajas-Espinosa, Alma; Perez-Aguilar, Sandra; Rosa, Ana Barba de la; Knabb, Maureen; Rubio, Rafael (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
Background: Ischemia and ischemia-reperfusion (I/R) are common clinical insults that disrupt the molecular structure of coronary vascular endothelial luminal membrane (VELM) that result in diverse microvasculature dysfunctions. However, the knowledge of the associated biochemical changes is meager. We hypothesized that ischemia and I/R-induced structural and functional VELM alterations result from biochemical changes. First, these changes need to be described and later the mechanisms behind be identified. Methods: During control conditions, in isolated perfused rat hearts VELM proteins were labeled with biotin. The groups of hearts were: control (C), no flow ischemia (I; 25 min), and I/R (I; 25 min, reperfusion 30 min). The biotinylated luminal endothelial membrane proteins in these three different groups were examined by 2-D electrophoresis and identified. But, it must be kept in mind the proteins were biotin-labeled during control. Results: A comparative analysis of the protein profiles under the 3 conditions following 2D gel electrophoresis showed differences in the molecular weight distribution such that MWC > MWI > MWI/R. Similar analysis for isoelectric points (pHi) showed a shift toward more acidic pHi under ischemic conditions. Of 100 % proteins identified during control 66% and 88% changed their MW-pHi during ischemia and I/R respectively. Among these lost proteins there were 9 proteins identified as adhesins and G-protein coupled receptors. General Significance: I and I/R insults alter MW-pHi of most luminal glycocalyx proteins due to the activation of non-specific hydrolyzing mechanisms; suspect metalloproteases and glycanases. This makes necessary the identification of hydrolyzing enzymes responsible of multiple microvascular dysfunctions in order to maintain the integrity of vascular endothelial membrane. VELM must become a target of future therapeutics.